Data Structures and Program Design Using C : A Self-Teaching Introduction - Malhotra, Dheeraj (Mercury Learning, 2019)
Designed to present fundamentals of data structures for beginners using the C programming language, this book integrates practical analogies using real world applications throughout to explain the technical concepts presented. -- Edited summary from book.
Keywords: C (Computer program language); elektronické knihy; electronic books